Paralelisme Konsumsi Bahan Bakar Pertalite Dengan Bahan Bakar Gas LPG 3 Kg Pada Mesin Bensin Pompa Air Starke Gwp50 - Akhmadi, Amin Nur; Usman, Mukhamad Khumaidi (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
A fuel is a compound that contains hydrocarbon elements. Pertalite is a fuel quality that has an Octane Research Number 90. LPG is made from petroleum gas material formed from Propane and Butane. The water pump drive engine is a pertalite-fueled internal combustion motor but may replace with LPG. The main reason is the cheap purchase price. Using LPG gas as a substitute for pertalite fuel is interesting research that will be conducted to conduct experiments testing pertalite fuel consumption with LPG gas. The results obtained in this study, namely using rice field water pumps with LPG gas fuel, resulted in lower consumption than pertalite fuel by 32% when without load and 28% when with the load.